2004
DOI: 10.1016/j.aap.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Crash reduction following installation of centerline rumble strips on rural two-lane roads

Abstract: Rural two-lane roads generally lack physical measures such as wide medians or barriers to separate opposing traffic flows. As a result, a major crash problem on these roads involves vehicles crossing the centerline and either sideswiping or striking the front ends of opposing vehicles. These types of opposing-direction crashes account for about 20% all fatal crashes on rural two-lane roads and result in about 4,500 fatalities annually in the US. The present study evaluated a potential engineering countermeasur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(69 citation statements)
references
References 6 publications
(4 reference statements)
1
67
0
1
Order By: Relevance
“…Similarly, speed violations of 6% or more are infrequent events at 120 km/h roads, and adding a financial incentive may not reduce speeding much further. Interestingly, accident statistics show that most fatal car accidents occur at undivided two-lane rural roads (Persaud et al, 2004), of which 80 and 100 km/h roads in the Netherlands are typical examples. As such, PAYD appears especially effective at roads where reduced speeding may result in relatively large safety gains.…”
Section: The Scope Of Payd As a Tool For Changing Driver Behaviormentioning
confidence: 99%
“…Similarly, speed violations of 6% or more are infrequent events at 120 km/h roads, and adding a financial incentive may not reduce speeding much further. Interestingly, accident statistics show that most fatal car accidents occur at undivided two-lane rural roads (Persaud et al, 2004), of which 80 and 100 km/h roads in the Netherlands are typical examples. As such, PAYD appears especially effective at roads where reduced speeding may result in relatively large safety gains.…”
Section: The Scope Of Payd As a Tool For Changing Driver Behaviormentioning
confidence: 99%
“…Until now, the main purpose of implementing chevrons and centre-line rumble strips in the UK has been to encourage a reduction in speed, for example on approach to villages, in the case of centre line rumble strips (Persaud, Retting & Lyon, 2004), or along motorways in the case of chevrons (Helliar-Symons & Butler, 1995). Likewise, Variable Message Signs are used mainly for information and advice on UK roads.…”
Section: Discussionmentioning
confidence: 99%
“…Research on rumble devices has shown a 15-20% reduction in fatigue-related accidents as a result of centre line rumble strips (Persaud, Retting & Lyon, 2004), whilst edge line rumble strips are thought to have reduced such accidents by around 40% (Mahoney, Porter & Donnell, 2003;Räsänen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…외국의 선행연구로는 회전교차로 구조변경 (Persaud et al, 2001;Brabander and Vereeck, 2007), 교 차로 운영방식의 개선 Persaud et al, 2003;Sayed and El-Basyoun, 2006), 교차로 접근로의 개선 (Yuan et al, 2001;Harwood et al, 2003), 고속도로 차로운영방식의 변 경 (Bauer et al, 2004), 노면안전시설 설치 (Persaud et al, 2004a), 노면요철포장의 설치 (Persaud et al, 2004b;Patel et al, 2007), 여러 가지 안전시 설개선 (Sharma and Datta, 2007) 되었다 (Benekohal and Hashmi.1992 ;Al-Masaeid, 1997 ;Griffith, 1999 ;Griffin and Flowers, 1997 ;Hauer, 1997). 본 연구에서는 Hauer ( …”
Section: 연구의 내용 및 방법unclassified